1974
DOI: 10.1083/jcb.60.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by Insulin of Rna Synthesis in Chick Fibroblasts

Abstract: After the addition of insulin to monolayers of chick fibroblasts previously incubated in serum-free medium, the rates of protein and RNA synthesis increase continuously during the first 8-10 h . Little stimulation of DNA synthesis or mitosis results with the addition of insulin alone in contrast to the addition of fresh serum which stimulates both markedly .The stimulation in RNA synthesis does not result from expansion of the nucleotide pool but is correlated with increases in RNA polymerase activity . All ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…These activities appear to have evolved in a distinct fashion (27). In most cases, pharmacologic amounts (>1 ug/ml or 25,000 ,U/ml) are required to elicit a proliferation response (7)(8)(9)28). It is unclear why such high concentrations are required for a biological response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These activities appear to have evolved in a distinct fashion (27). In most cases, pharmacologic amounts (>1 ug/ml or 25,000 ,U/ml) are required to elicit a proliferation response (7)(8)(9)28). It is unclear why such high concentrations are required for a biological response.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, many hormones have been shown to augment erythroid colony formation in culture (4)(5)(6). One such hormone, insulin, is a polypeptide that stimulates DNA synthesis and mitosis by cross-reactivity with receptors for structurally related peptides (insulinlike growth factors [IGFs]') (7)(8)(9). Recently, we showed that the secretory protein platelet-derived growth factor (PDGF) is also a serum determinant of optimal human bone marrow colony-forming unit-erythroid (CFU-E) and burstforming unit-erythroid (BFU-E) proliferation (10).…”
Section: Introductionmentioning
confidence: 99%
“…Primary cultures of chick embryo cells, prepared from I I-day old embryos, were plated at a cell density of 4 • 105 cells/cm ~ in 1-and 8-ounce bottles and allowed to reach confluence in Eagle's minimum essential medium (MEM) supplemented with 3% calf serum (2,22). Monolayers were then washed free of serum medium with MEM and incubated in serum-free MEM for 24 b before the experiment.…”
Section: Primary Cell Culturesmentioning
confidence: 99%
“…Hormonal stimulation of RNA synthesis. Quiescent cultures of chick embryo cells were exposed to insulin, insulin plus hydrocortisone, hydrocortisone, or serum for 8 h. During the last hour, [SH]uridine (20 #Ci/ml of medium) was introduced and RNA was extracted as previously described (2). Optical densities (260/280) of the RNA preparations were determined and 10 #g of RNA was applied to individual acrylamide-agarose gels for electrophoresis.…”
Section: -5s 2s 3'0 Io 15 6'o 15 R Rmentioning
confidence: 99%
“…Insulin, whose secretion is caused by elevated protein intake and glucose levels in the blood, is required for normal growth. Insulin increases rate of amino acid incorporation into muscle protein (Manchester and Krahl, 1959;Snipes, 1967), the proportion of ribosomes attached to itiRNA, polysome formation (Manchester, 1974;Stirewalt et al, 1967;Wool et al, 1968;Young et al, 1971), the biosynthetic activity of ribosomes in a cell-free system (Wool and Cavicchi, 1966), the rate of amino acid binding to tRNA, and stimulates RNA polymerase activity (Baseman et al, 1974).…”
Section: Such Muscles Have Different Metabolic Activities Accordingmentioning
confidence: 99%